Birthweight and the risk of atopic diseases: the ISAAC Phase III study. Issue 3 (20th February 2014) - Mitchell, Edwin A.; Clayton, Tadd; García‐Marcos, Luis; Pearce, Neil; Foliaki, Sunia; Wong, Gary; ,
Abstract Background The association between birthweight and asthma, eczema and rhinoconjunctivitis is conflicting. Aims To examine the association between birthweight and symptoms of asthma, eczema and rhinoconjunctivitis. Methods Parents or guardians of children aged 6–7 yr completed written questionnaires about symptoms of asthma, rhinoconjunctivitis and eczema, and several risk factors, including birthweight. Results There were 162, 324 children from 60 centres in 26 countries. Low birthweight (<2.5 kg) was associated with an increased risk of symptoms of asthma (current wheeze odds ratio = 1.20; 95% confidence interval = 1.12–1.30). Low birthweight was associated with a lower risk of eczema ever. Low birthweight was not associated with rhinoconjunctivitis. Large babies (birthweight ≥4.5 kg) were not associated with any of these outcomes. Conclusions This study has confirmed that low birthweight is a risk factor for symptoms of asthma, but not for rhinoconjunctivitis. The findings for eczema are equivocal.